Terapi Musik Baby Shark Mampu Menurunkan Kecemasan pada Anak Usia Prasekolah - Elfira Awalia Rahmawati (Journal of Telenursing (JOTING), 2020)
This study aims to determine the effect of baby shark music therapy on preschoolers' anxiety at Pelni Hospital in Jakarta. This research method is a simple descriptive method with a research design that is a case study. The results of case study research with baby shark music therapy have an effect that can reduce the level of anxiety in children while in the hospital. There was a decrease in anxiety in both study subjects, from moderate anxiety at the beginning of the assessment to mild stress and no strain on the third day of the study. In conclusion, baby shark music therapy can reduce anxiety levels in preschool children. Keywords: Baby Shark, Hospitalization, Anxiety, Preschool, Music Therapy